Pelatihan Manajemen Arsip dan Dokumen untuk Mendukung Kompetensi Administrasi di SMK Garuda Nusantara - Arif Siswandi; Yos Soejarminto; Elkin Rilvani; Arif Tri Widiyatmoko; Rizki Muhammad; Novi Wulandari (VINICHO MEDIA PUBLISINDO, 2026)
Archive and document management is one of the essential competencies required for vocational high school (SMK) graduates, particularly in the field of office administration. However, based on observations conducted at SMK Garuda Nusantara, archive management is still carried out conventionally, lacks standardized Standard Operating Procedures (SOPs), and has limited utilization of digital technology for document management. These conditions have resulted in inadequate student competence in managing archives systematically and professionally. This community service program aims to enhance students' competencies in archive and document management through theory- and practice-based training, the development of archive management SOPs, the introduction of electronic archive (e-archive) systems, and implementation assistance. The program employs a participatory approach consisting of socialization, needs assessment, training, technology implementation, mentoring, and evaluation. The expected outcomes include improved student knowledge and practical skills, the development of archive management training modules and SOPs, enhanced digital literacy in document management, and the integration of a practice-based learning model that can be sustainably implemented within the school environment. This program is expected to improve students' readiness to meet the demands of modern administrative workplaces.